2019
DOI: 10.1055/a-1010-6505
|View full text |Cite
|
Sign up to set email alerts
|

School Bag Packs and Associated Problems among School Going Children

Abstract: Objective The objective of this study was to assess school backpacks and associated problems across school going children aged 8–12 years in Lahore, Pakistan. Self-perceived pain related to bag pack use, correlation between self-reported pain and perceived weight of bag pack, duration of bag pack carriage and the method of bag pack carriage were evaluated. Methodology A cross-sectional survey was conducted on 3500 students from different private schools across Lahore. Both male and female students from the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Consequently, parents and healthcare professionals must pay attention to the weight of backpacks, given their diverse impacts on spinal health under various loading conditions. Furthermore, there is a continuous rise in the prevalence of pain associated with spinal deformities [15]. The increasing occurrence of neck pain, forward tilt, rounded shoulders, and even lumbar vertebral damage due to overweight backpacks [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, parents and healthcare professionals must pay attention to the weight of backpacks, given their diverse impacts on spinal health under various loading conditions. Furthermore, there is a continuous rise in the prevalence of pain associated with spinal deformities [15]. The increasing occurrence of neck pain, forward tilt, rounded shoulders, and even lumbar vertebral damage due to overweight backpacks [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies showed that load carriage affects walking posture and gait and may even cause trunk bending and spinal asymmetry [ 2 , 3 ], leading to an increased incidence of lower extremity injuries, and even back pain [ 4 ]. Therefore, experts have suggested that the backpacks worn by elementary and growing students should not be too heavy [ 5 ], with one study stating that it should not exceed 15% of the body weight [ 6 ]. The habitual use of backpacks has become fairly common in the daily life of people of many professions, including office workers, students, and the elderly, all of whom can be seen walking or running with a backpack.…”
Section: Introductionmentioning
confidence: 99%